2010
DOI: 10.1007/s10620-010-1261-y
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Insufficiency in Adult Celiac Disease: Do Patients Require Long-Term Enzyme Supplementation?

Abstract: Fecal elastase-1 is useful in identifying exocrine pancreatic insufficiency in adult celiac patients with diarrhea. Our longitudinal data suggests that pancreatic enzyme supplementation could be discontinued in a substantial proportion of patients as symptoms improve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…Milder cases of pancreatic insufficiency (i.e., insufficient release of pancreatic proteases, assessed by fecal elastase-1 (E1) concentration (< 200 μg/g stool)) are common in gastrointestinal disorders such as celiac disease (Carroccio et al, 1991; Carroccio et al, 1994; Nousia-Arvanitakis et al, 1999; Evans et al, 2010), Crohn’s disease and ulcerative colitis (UC) (Maconi et al, 2008), giardiasis and cow milk-related enteropathy (Walkowiak and Herzig, 2001) and irritable bowel syndrome (Leeds et al, 2010) (Figure 1B). Mucosal damage and villous atrophy, as seen in most of these conditions, can decrease CCK release from I cells in the crypts and villi of the duodenum and jejunum, which results in pancreatic insufficiency.…”
Section: Consumers Differ In Digestive Capacitymentioning
confidence: 99%
“…Milder cases of pancreatic insufficiency (i.e., insufficient release of pancreatic proteases, assessed by fecal elastase-1 (E1) concentration (< 200 μg/g stool)) are common in gastrointestinal disorders such as celiac disease (Carroccio et al, 1991; Carroccio et al, 1994; Nousia-Arvanitakis et al, 1999; Evans et al, 2010), Crohn’s disease and ulcerative colitis (UC) (Maconi et al, 2008), giardiasis and cow milk-related enteropathy (Walkowiak and Herzig, 2001) and irritable bowel syndrome (Leeds et al, 2010) (Figure 1B). Mucosal damage and villous atrophy, as seen in most of these conditions, can decrease CCK release from I cells in the crypts and villi of the duodenum and jejunum, which results in pancreatic insufficiency.…”
Section: Consumers Differ In Digestive Capacitymentioning
confidence: 99%
“…In this paper, the first longitudinal study to follow-up adult celiac patients with low fecal elastase levels [13], 20 patients with diagnosed celiac disease who remained symptomatic with chronic diarrhea and a low FE-1 despite a gluten-free diet (GFD), were commenced on pancreatic enzyme therapy (PET). Patients were reassessed at 6 and 12 months, and then annual intervals over a period of 4 years.…”
mentioning
confidence: 99%
“…Celiac disease is frequently associated with PEI,70,71 possibly because of increased immune activity in the intestinal tract. Evans et al70 showed that in a study of 20 patients with celiac disease, diarrhea was improved in 19 patients given PERT at a mean dose of 45,000 lipase units/day.…”
Section: Extrapancreatic Diseases and Conditionsmentioning
confidence: 99%
“…Celiac disease is frequently associated with PEI,70,71 possibly because of increased immune activity in the intestinal tract. Evans et al70 showed that in a study of 20 patients with celiac disease, diarrhea was improved in 19 patients given PERT at a mean dose of 45,000 lipase units/day. Leeds et al72 also showed that low fecal elastase content is more common in patients with celiac disease and chronic diarrhea, and that PERT in combination with a gluten-free diet reduced stool frequency from four per day to one.…”
Section: Extrapancreatic Diseases and Conditionsmentioning
confidence: 99%